GREEN MARKETING STRATEGIES AS A COMPETITIVE ADVANTAGE: ANALYZING THE IMPACT ON CUSTOMER LOYALTY IN THE ISLAMIC BANKING SECTOR - Jayusman, Hendra; Khotimah, Siti; Jannah, Wardatul; Rupa, Martina Kaisriani; Nurlaela, Fitri (Branding: Jurnal Manajemen dan Bisnis, 2024)
Green marketing has become an important strategy for Islamic banking in facing changing customer preferences that are increasingly concerned about sustainability. The implementation of this strategy not only increases competitiveness but also strengthens the image and reputation of banks amidst the increasing demands for more responsible business practices. However, Islamic banking faces various challenges in implementing green marketing strategies, including regulatory constraints, investment, and customer awareness levels. This study aims to analyze the impact of green marketing strategies on customer loyalty in the Islamic banking sector and how this strategy can be used as a competitive advantage. This study uses a qualitative approach by analyzing data from various sources, including previous studies, industry reports, and relevant literature. The data collected is then processed and analyzed systematically to identify patterns and factors that influence the effectiveness of green marketing in Islamic banking. The results of the study show that green marketing contributes positively to customer loyalty by increasing trust and emotional attachment to the bank. In addition, this strategy strengthens the competitiveness of Islamic banking compared to banks that still apply conventional approaches. However, to ensure the sustainability of its benefits, banks need to adapt to technological developments, increase transparency, and overcome obstacles that arise in the implementation of green marketing.